Realizing Rights Through Social Guarantees : An Analysis of New Approaches to Social Policy in Latin America and South Africa - World Bank (Washington, DC, 2012)
This paper examines the experiences in four Latin American countries and South Africa in the application of a human rights approach to social policy. The paper applies an analysis based on a social guarantees framework -- an innovative approach to integrate a rights-based perspective into social policy. The social guarantees approach moves beyond a purely normative framework to give concrete meaning to economic, social, and cultural rights and hence to allow for their operationalization into policies and programs. This document suggests that a social guarantee approach can be used to strengthen the delivery and monitoring of social programs. Firstly, it implies an institutional design that emphasizes synergy and coordination among agencies and providers to help social programs achieve their full potential. Secondly, this approach contributes to reducing gaps in opportunity among citizens by promoting universal access to, and a basic quality standard for, essential services. Thirdly, the social guarantee approach contributes to strengthening democratic governance, as it requires the achievement of a non-discriminatory agreement among all members of society as to the level of basic entitlements of each individual or collective. In other words, social guarantees are safeguards that society provides to all its members, ensuring their access to essential opportunities and well-being.